El papel conceptual y teórico de la actividad académica para la comprensión de la investigación en el aprendizaje digital - West, Richard (Revista de Educación a Distancia (RED), 2020)
Special Issue Introduction The goal of research is to understand our world and the people in it. This understanding comes through a variety of methods and strategies that each uncover a different layer of knowledge that can contribute to this overall understanding. As researchers, we are much like a young child seeking to understand their surroundings by first touching a new toy, then lifting it, then shaking it, then even tasting it! Each of these strategies tells the child a little more about the object. Similarly, as we seek to understand and influence our world, we need the knowledge gained from a wide variety of scholarly methods. The articles that make up this special issue are intended to bring that mission and goal closer together.